RANCANG BANGUN ALAT FIXED STEERING ROLLER UNTUK MENCEGAH MISTRACKING PADA BELT CONVENER - Budiharja, Yuniar Anis; Darmanto, Seno; Mangestiyono, Wiji (universitas teuku umar, 2022)
Fix the Steering Roller, Where the purpose of making this tool is to prevent mistracking on the Belt Conveyor. The manufacture of this tool was carried out considering the need for PLTU Nagan Raya 2 x 110 MW. PLTU itself is a coal-fired power plant where all coal needs from the Jetty to the Bunker are transported using a Belt Conveyor. In fact, when transporting coal using a Belt Conveyor, there are a lot of coal spills on the Belt side so that it really interferes with the work process of the conveyor belt itself. The spill was caused by a tilted conveyor belt or it could be called mistracking. Therefore, the manufacture of this tool is a solution to prevent mistracking where the installation of this tool is very easy and does not interfere with the existence of the Belt Conveyor equipment itself.